DEVELOPMENT OF PEDAGOGICAL IDEAS DURING THE YEARS OF INDEPENDENCE - Norboyeva , Jang’il (Journal of Pedagogical and Philological Research, 2026)
This article examines the development of pedagogical ideas, conceptual changes in the field of education, and the evolution of pedagogical strategies in Uzbekistan since the achievement of independence. The research analyzes the processes of abandoning the standardized education of the former Soviet era and restoring our national pedagogical heritage, particularly the educational ideas of Eastern thinkers and representatives of the Jadidism movement. Furthermore, the article highlights the integration of modern Uzbek pedagogy into the global education system, student-centered educational technologies, and the influence of the "Third Renaissance" idea on the content of education.